SARS CoV-2 pandemic mars the world hepatitis day theme 2020 of "Hepatitis free future in India" While Hepatitis -C, Research wins Nobel Price-2020 - K Suresh (Open Journal of Hepatology - Peertechz Publications, 2020)
The best news of the year 2020 about Hepatitis is the announcement of the winners of the prize for Medicine or Physiology for the discovery of the Hepatitis C virus to Americans Harvey J. Alter and Charles M. Rice, and British scientist Michael Houghton on Monday the 5th October 2020. Second good news is Global hepatitis strategy- 2020 endorsed by all WHO Member States, aiming to reduce new hepatitis infections by 90% and deaths by 65% by 2030. World Hepatitis Day (WHD) 2020 on 28 July intended to bring the world together under a single theme of 'Hepatitis free future' by finding the 'Missing Millions' and raising awareness to influence real change.  Hepatitis is an inflammation of the liver that can cause a range of health problems and can be fatal. There are five main strains of the hepatitis virus, referred to as types A, B, C, D and E. While they all cause liver disease, they differ in modes of transmission, severity of the illness, geographical distribution, and prevention methods. Recent estimates indicate that worldwide there are over 345 million infections of hepatitis all varieties put together and 1.5 million deaths each year. Majority of these cases belong to HBV, followed by HCV and HDV. WHO estimates that, there are 320 million people worldwide to be living with viral hepatitis B & C and most of them are unaware, as testing and treatment remains beyond their reach? Introduction and Scaling up of infant vaccination have demonstrated a reduction of HBV prevalence.  Hepatitis A Virus (HAV) and Hepatitis E Virus (HEV) are predominantly enterically transmitted pathogens and are responsible to cause both sporadic infections and epidemics of acute viral hepatitis. Public health measures to improve sanitation and provide safe drinking water for preventing HAV and HEV are in progress.  HBV, HCV and HDV are predominantly spread via parenteral route and are notorious to cause chronic hepatitis which can lead to grave complications including cirrhosis of liver and hepatocellular carcinoma.  The Government of India has conveyed a political intent by setting up a comprehensive action plan- 'National Viral Hepatitis Control Program (NVHCP)'. This is an integrated approach for prevention and control of viral hepatitis, aiming to end viral hepatitis by 2030 as envisaged in National Health Policy 2017.  However, the good intentions of reaching target are not matched by resources and execution of plan. To add to this perineal systemic problem, the Jugaad approach for Covid- 19 Pandemic management, since March 2020, the entire Government machinery is being mobilized for firefighting the pandemic, that has resulted in all other public health programs having a setback for want of resources, monitoring and requisite push. There are many unfinished tasks left in prevention and elimination of viral hepatitis in developing countries, especially India. The prevailing water and sanitation issues continue haunt the country with HAV and HEV outbreaks. HAV vaccination strategies need redefining because of changing epidemiology. HEV vaccine should be made available in India.  Encouraging voluntary blood donation and safe renal dialysis are in infancy and Individual blood and organ donors' nucleic acid testing (NAT) detects infection for HIV, HBV, and HCV  is yet to be used as a screening tool. For the management of chronic HBV infection, treatment should be targeted at those with highest risk of disease progression, based on the detection of persistently raised alanine transaminase (ALT) levels and HBV DNA more than 20,000 IU/ml in those older than 30 years.   In this article I have captured hepatitis infection status, major challenges in achieving hepatitis free India by 2030 competing with Covid-19 pandemic